A Rare Case of Extra Dural Dorsal Meningioma; Case Report and Analytique Review of Literature about 77 Cases - Koffi, Niamien Patrice; Salami, Mohcine; Elkacemi, Inas; Miloudi, Gazzaz (International Journal of Innovative Research in Medical Science, 2021)
Spinal meningiomas are usually intra dural tumors, the purely extra dural localization is exceptional, they are easily mistaken for malignant tumor resulting in inadequate management. Only 77 cases have been reported in the literature. Less than 28 cases have been confirmed after durotomy since 1898. We report a new observation followed by an analytical review of the literature with a study of the socio-epidemiological, radiological parameters and of the neurosurgical and progressive management of extra dural spinal meningiomas. Observation: a 57-year-old, female patient with no medical history was admitted to our training for slow dorsal spinal cord compression progression since 06 months. Neurological examination found FRANKEL stage C paraplegia, higher level D7 hypoaesthesia without sphincter disorders. The medullary MRI objectified an intraspinal process of 1.5x2x1cm, well limited, of the right posterolateral of D8-D9 causing compression of the dorsal cord with an intramedullary hyper signal in T2. The D8-D9 laminectomy was performed. Surgical exploration found an extra dural lesion without intra dural extension. The excision was macroscopically complete. Histological examination was in favor of a benign meninigothelial. The post-operative course was marked by a partial and progressive recovery of the neurological deficit and no recurrence. Discussion: the retrospective analysis of literature about 49 publications was founded that, the incidence in 1933 by Elsberg was 5.5%, Haft in 1963 found 3.5%. In 2020 our study found 3.46% of all spine meningioma. The mean age is 44.19 years [8 years -85 years] with a female predominance of 2/1. The mode of revelation is in 11.53% of fortuitous discovery, in 59.93% by the high state of spinal cord compression stage C of FRANKEL. The topography is dorsal = 51.31%, cervical = 44.76%. MRI scan has been use since 1996 at 67.60%. Laminectomy was performed in 71.79% with durotomy in 11%. The excision is complete with SIMPSON I in 70% and SYMPSON III in 27%. The predominant histological is a grade 1 of meningioma = 73.41%, grade 2 = 6.32%, grade 3 = 1.26% in 19 % meningioma was not specified by the authors. Conclusion: The prognosis of extra dural spinal meningiomas according to our study is good overall with only 3 cases of recurrence of spinal meningioma in 36 patients, or 8.33% after a mean follow-up of 31.59 months [1 -168 months] with P=0,012.